Correspondence between the self-dual model and the topologically massive electrodynamics: A new view - Pimentel, B. M. [UNESP] (2013)
Following the study of the Topologically Massive Theories under the Hamilton-Jacobi, we now analyze the constraint structure of the Self-Dual model as well as its correspondence with the Topologically Massive Electrodynamics. © 2013 American Institute of Physics.